2007
DOI: 10.1634/stemcells.2007-0550
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Stimulates Mouse Embryonic Stem Cell Proliferation by Cooperation of Ca2+/Protein Kinase C and Epidermal Growth Factor Receptor As Well as Gli1 Activation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 56 publications
3
55
0
3
Order By: Relevance
“…Furthermore, here, we show that another selective Notch inhibitor, L-685,458, is equally ineffective in impairing both GBM TIC viability and Notch1 processing, even when used at concentrations higher than the ones previously reported as effective (42)(43)(44)(45). Interestingly, the potency in growth suppression of DAPT was reported as mild compared with LLNle also in a different cellular system (46).…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, here, we show that another selective Notch inhibitor, L-685,458, is equally ineffective in impairing both GBM TIC viability and Notch1 processing, even when used at concentrations higher than the ones previously reported as effective (42)(43)(44)(45). Interestingly, the potency in growth suppression of DAPT was reported as mild compared with LLNle also in a different cellular system (46).…”
Section: Discussionmentioning
confidence: 59%
“…The universal character of second-messenger signaling predicts that this pathway is common to different cell types, although different classes of cells may exhibit distinctive second-messenger dynamics (51,52). It will be of interest to investigate how these steps of decoding Shh signaling are connected to other elements of its canonical pathway and to determine the mechanisms by which the interactions between Shh, IP3, and Ca 2+ are interpreted and translated into expression of specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the activation of the EGFR pathway resulted in the stimulation of transcription factors such as activator protein 1 family member JUN that cooperated with GLI1 and/or GLI2 activators for triggering selective expression of target gene products involved in the oncogenic transformation of BCC cell lines (Schnidar et al, 2009). Likewise, the stimulation of the Hh pathway can also modulate the expression and activities of EGFR signaling elements (Bigelow et al, 2005;Mimeault et al, 2006;Pasca di Magliano et al, 2006;Heo et al, 2007). For instance, it has been observed that the constitutive SHH expression was associated with an enhanced phosphorylation of EGFR in mouse embryonic stem cells and human HaCaT keratinocytes as well as an increase of collagen matrix invasion of HaCaT keratinocytes (Bigelow et al, 2005;Heo et al, 2007).…”
Section: B Cross-talks Between the Hedgehog And Epidermal Growth Facmentioning
confidence: 99%